2011
DOI: 10.1007/s12257-010-0418-z
|View full text |Cite
|
Sign up to set email alerts
|

Multisubstrate monod kinetic model for simultaneous degradation of chlorophenol mixtures

Abstract: Chlorophenols (CPs) are persistent and highly toxic compounds rated as priority pollutants by the Environmental Protection Agency (EPA). Frequently, these compounds are present as mixtures of CPs in industrial wastewaters. Therefore the study of biodegradation on mixed pollutants is an important aspect of biodegradation and wastewater treatment. In this work, we studied the multisubstrate degradation of CPs by a mixed culture of Pseudomonas aeruginosa and a novel Acromobacter sp. capable of using pentachloroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 27 publications
(36 reference statements)
1
35
1
1
Order By: Relevance
“…The substrate to biomass yield coefficients based on total CP degradation are also shown in Table 1. These values are higher than those previously reported by Durruty et al (2011) for the same strain and acclimated condition, exposed to similar CP concentrations but with lower biomass concentration. These results support the observation of Moreno-Andrade and Buitrón (2003), who observed that growth inhibition is not only a function of the initial substrate concentration, but also of the initial biomass concentration.…”
Section: Resultscontrasting
confidence: 76%
See 3 more Smart Citations
“…The substrate to biomass yield coefficients based on total CP degradation are also shown in Table 1. These values are higher than those previously reported by Durruty et al (2011) for the same strain and acclimated condition, exposed to similar CP concentrations but with lower biomass concentration. These results support the observation of Moreno-Andrade and Buitrón (2003), who observed that growth inhibition is not only a function of the initial substrate concentration, but also of the initial biomass concentration.…”
Section: Resultscontrasting
confidence: 76%
“…The effect of a secondary chlorophenol on the removal of another chlorophenol present in the mixture has been investigated using batch Tobajas et al, 2010) and fed-batch systems (Quan et al, 2005;De Los CobosVasconcelos et al, 2006). In previous work (Durruty et al, 2011), it has been demonstrated that the presence of 2,4,6-TCP …”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…used in this study was isolated from soil and capable of degrading chlorophenols (Murialdo et al, 2003;Wolski et al, 2006;Durruty et al, 2011aDurruty et al, , 2011b. Microorganisms were stored and grew as detailed in a previews work (Nisenbaum et al, 2013).…”
Section: Bacterial Strains and Growth Mediamentioning
confidence: 99%